Abrasive Machining of Ti6Al4V Alloy - Lattner, Radek; Holešovský, František; Karel, Tomáš; Lattner, Michal (Manufacturing Technology Journal, 2015)
This paper deals with evaluation of ground surface of Ti6Al4V alloy according to surface roughness. This titanium alloy has large scale of utilization, it is used for implants and surgical instruments. Significant problem during grinding of titanium alloys is generation of large amount of heat which can cause surface cracks, increase hardness of surface and increase of tool wear. Each specimen was ground on surface grinding machine by diferent cutting conditions. The roughness parameters Ra, Rq, Rz and Rt were measured five times on each specimen in each axis (axis y - direction of feed rate, axis x - perpendicular to the feed rate). The values of the roughness parameters (Ra, Rq, Rt and Rz) are presentated in the graphs where we can see the influence of the cutting conditions on these roughness parameters.
Keywords: grinding; titanium alloy; roughness; abrasive